2017
DOI: 10.3390/ijms18092013
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of Axon Extension for Human iPSC-Derived Retinal Ganglion Cells by a Nano-Imprinted Scaffold

Abstract: Optic neuropathies, such as glaucoma and Leber’s hereditary optic neuropathy (LHON) lead to retinal ganglion cell (RGC) loss and therefore motivate the application of transplantation technique into disease therapy. However, it is a challenge to direct the transplanted optic nerve axons to the correct location of the retina. The use of appropriate scaffold can promote the proper axon growth. Recently, biocompatible materials have been integrated into the medical field, such as tissue engineering and reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Although broad and overlapping, these LM stages hold practical importance when designing, conducting and interpreting experiments involving hPSC-derived retinal organoids. For example, studies targeting RGCs are best performed at stage 1 or early stage 2 when they are relatively abundant and their processes project to the surface, which facilitates axonal outgrowth after attachment of the RGCs to substrate (Yang et al, 2017;Kobayashi et al, 2018;Langer et al, 2018). The cause of the deterioration and disorganization of RGCs at later stages is not completely clear, but, among other factors, it could be due to an absence of post-synaptic forebrain targets, lack of inner retinal structure, and/or insufficient metabolic support.…”
Section: Discussionmentioning
confidence: 99%
“…Although broad and overlapping, these LM stages hold practical importance when designing, conducting and interpreting experiments involving hPSC-derived retinal organoids. For example, studies targeting RGCs are best performed at stage 1 or early stage 2 when they are relatively abundant and their processes project to the surface, which facilitates axonal outgrowth after attachment of the RGCs to substrate (Yang et al, 2017;Kobayashi et al, 2018;Langer et al, 2018). The cause of the deterioration and disorganization of RGCs at later stages is not completely clear, but, among other factors, it could be due to an absence of post-synaptic forebrain targets, lack of inner retinal structure, and/or insufficient metabolic support.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of physical support possibly limits the survival and differentiation of the injected cells. Some recent studies demonstrated that engineered scaffolds or biomaterials can stimulate RGC axon outgrowth in vitro (Kador et al, 2014;Sluch et al, 2015;Li et al, 2017;Yang et al, 2017). Introducing a RGC-scaffold biomaterial into the eye would be a real progress compared to an injection of cell suspension as reported recently in rabbits and monkeys (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Photoreceptor transplantation with biomaterials. Both synthetic polymers and biological materials can be used in the fabrication of scaffolding structures for photoreceptors implants: natural materials like alginate, collagen, etc., are suitable for imitating natural architectures (Ramakrishna et al, 2001); synthetic polymers, such as poly-caprolactone (PCL) and poly (lacticco-glycolic) acid (PLGA), offer higher mechanical strength and controllable degradation rates (Chen et al, 2011) although the latter usually cause less biological activity (Yang et al, 2017). Scaffolds for retinal progenitor cells (RPCs) transplants can be cylindrical, mimicking the vertical disposition of cells in the retina, fibrous, mimicking the microstructure of the extracellular matrix or made by hydrogels, to mimic the mechanical properties of the retina (Kador and Goldberg, 2012).…”
Section: In Vitro and Pre-clinical Trialsmentioning
confidence: 99%
“…On the other hand, the dimensional conformation or porosity of the scaffold seems to promote the union and subsequent differentiation and orientation of the RPCs (Lee Ventola, 2014). Other studies defend the idea that scaffold topography influences orientation, because of its positive influence on differentiation, morphology, proliferation, migration and adhesion of the cells (Ramakrishna et al, 2001;Kador et al, 2016;Yang et al, 2017). Scaffolds can actively interact with different cellular components.…”
Section: Biomaterials and Improvement Of Cell Survivalmentioning
confidence: 99%